Nano CuO: Electrochemical sensor for the determination of paracetamol and d-glucose. (November 2019) - Avinash, B.; Ravikumar, C.R.; Kumar, M.R. Anil; Nagaswarupa, H.P.; Santosh, M.S.; Bhatt, Aarti S.; Kuznetsov, Denis
Abstract: A green combustion method using Aloe vera latex as a fuel was employed to synthesize nanocrystalline cupric oxide (CuO). The nanocrystalline nature and phase of CuO was confirmed by powder X-ray diffraction. Applying the Kubelka–Monk function to diffuse reflectance spectra showed the band gap of CuO to be 1.632 eV. Paracetamol andd -glucose in 1 M KOH solution were sensed using a carbon paste electrode modified using CuO nanoparticles (NPs). The cyclic voltammetry results suggest that CuO NPs possess superior electrochemical properties due to a lower value of the difference between oxidation and reduction potential (EO -ER ). The proton diffusion coefficient for CuO electrode material was1.5047 × 10 −5 cm 2 s −1 . Electrochemical impedance and Bode studies confirmed that the charge-transfer resistance value of CuO NPs was on the lower side due to the phase angle (55°) being near to ф  = ᴨ/2. The electrochemical behavior indicates that CuO is a promising electrode material for sensing molecules such as paracetamol and glucose. Highlights: Nano CuO sample issynthesizedbya novel green combustion method. Cyclic voltammetry is used to sense paracetamol andd -glucose. CuO nanoparticles possess superior electrochemical properties. The proposed sensor reveals a high sensitivity for paracetamol andd -glucose.